La ciudad en la Literatura del Siglo de Oro - Cámara, Alicia (Anales de Historia del Arte, 2008)
The descriptions of cities by 16th and 17th -century writers select aspects that approximate those of the ideal city formulated since the Renaissance. Cleanliness, public works and great buildings, principal squares, nature in the city, the ancientness and excellence of the citizens are some of themes found in their books.
Keywords: Town planning; Golden Age; Ideal city; Main square; Madrid; Toledo; Valladolid; Zaragoza; Sevilla; Denia; Medina del Campo; Jaén; Valencia; Cuenca; Granada; Málaga; Murcia; Salamanca